Analysis Of A Judge’s Progressive Decision In The Pretrial Examination On The South Jakarta District Court Decision No.04/Pid.Prap/2015pn.Jkt.Sel - Weldy Jevis Saleh; Upik Mutiara (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose of the study: This paper aims to provide an analytical review of the judicial progressive thoughts in the pretrial process in Decision No. 04/Pid.Prap/2015/PN.Jkt.Sel. Methodology: This legal research used a normative juridical approach. The writers used the literary approach by studying books and legal regulations related to this research. Results: The judges’ basis of thought delivered in Decision No. 04/Pid.Prap/2015/PN.Jkt.Sel was part of the judicial authority to make laws (judge-made laws). This is so that the law can provide the value of justice or certainty. But in this context, the method used by the judges was legal interpretation due to